Autoantibodies in Autoimmune Hepatitis: Can Epitopes Tell Us about the Etiology of the Disease? - Christen, Urs; Hintermann, Edith (Frontiers in Immunology, 2018)
Autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC), are serious autoimmune liver diseases that are characterized by a progressive destruction of the liver parenchyma and/or the hepatic bile ducts and the development of chronic fibrosis. Left untreated autoimmune liver diseases are often life-threatening and patients require a liver transplantation to survive. Thus, an early and reliable diagnosis is paramount for the initiation of a proper therapy with immunosuppressive and/or anticholelithic drugs. Besides the analysis of liver biopsies and serum markers indicating liver damage, the screening for specific autoantibodies is an indispensable tool for the diagnosis of autoimmune liver diseases. Such liver autoantigen-specific antibodies might be involved in the disease pathogenesis and their epitope specificity may give some insight into the etiology of the disease. Here, we will mainly focus on the generation and specificity of autoantibodies in AIH patients. In addition, we will review data from animal models that aim toward a better understanding of the origins and pathogenicity of such autoantibodies.